Plática as a Methodology for Creating Counterspace in Online Teaching and Beyond - Vazquez Dathe, Magdalena; Brassington, Lou Ellis; Rice, Mary Frances (Online Learning, 2025)
In this paper, we reflect upon and (re)analyze a self-study of teacher education practices (S-STEP) inquiry that was focused on deconstructing the circumstances of loss and anxiety we experienced during the pandemic years and onward as we conducted our online teacher education classes. In seeking to repair, restore, and heal, we engaged with Chicana feminist thinking and centered on the methodology of plática. Our pláticas created intimate spaces to address entangled laborings, emotional work, and consider ways to address our statuses within the hierarchy of our institution. Based on our experiences teaching online during the pandemic and beyond, we illustrate the potential of plática as a methodology for intentionally cultivating counterspaces directed at fostering healing and facilitating relational engagement—not only for online teacher educators of varied backgrounds, but across diverse fields and instructional formats. Plática methodology offers additional opportunities for transformative framing to reimagine pedagogical connections between students and instructors.